The Doctrine of the Freedom of Contract (Hurriyyat al-Ta‘aqud) in Islamic Mu‘amalat: An exposition on the concept and rules of the contract of muqawalah in the construction industry - Abdullah, Atikullah (Islamic Studies, 2011)
The doctrine of Hurriyyat al-ta‘aqud or freedom of contract is a point of disagreement among fiqhi scholars. Nevertheless, in reality, the present trend in Islamic mu‘amalatshows that freedom of contract is a very important doctrine for Muslims that allows them room to utilize their creativity and wisdom to fulfill their obligations. This trend is clearly evident with the emergence of many types of new contracts — either totally brand new contracts without any traces of the classical fiqh literature or modified forms of original contract. Among the new contracts that have emerged recently is the muqawalah. This paper, thus, seeks to discuss the concept of the muqawalah contract as a clear manifestation ofthe doctrine of freedom of contract in Islamic mu‘amalat. In doing so, the writer only refers to fiqh treatises and literature that are widely circulated amongst the four Sunni schools of Islamic law. This is notto deny the importance of the contributions of the Shi‘i schools in the development of Islamic law. Nevertheless, the underlining principles of mu‘amlat in the main Shi‘i school of law namely the Ja‘fariyyah or the Imamiyyah can hardly be differentiated from Sunni schools of law. This paper argues that the contract of muqawalah offers a good and viable approach to solve the problems that occurs in the construction industry and is indeed a clear proof of the dynamism of Islamic mu‘amalat.